Disease-free interval and tumor functional status can be used to select patients for resection/ablation of liver metastases from adrenocortical carcinoma: insights from a multi-institutional study. Issue 1 (January 2020) - Ayabe, Reed I.; Narayan, Raja R.; Ruff, Samantha M.; Wach, Michael M.; Lo, Winifred; Nierop, Pieter M.H.; Steinberg, Seth M.; Ripley, R. Taylor; Davis, Jeremy L.; Koerkamp, Bas G.; D'Angelica, Michael I.; Kingham, T. Peter; et al.
Abstract: Background: Adrenocortical carcinoma (ACC) is an aggressive malignancy that frequently metastasizes to the liver. Given the limitations of systemic therapy in this setting, we sought to determine characteristics associated with a two-fold increase in survival with resection/ablation compared to that reported with chemotherapy alone (∼12 months). Methods: Patients who underwent resection/ablation at our institutions for ACC liver metastases were identified. Those who survived 12–24 months after metastasectomy were excluded, as the aim was to characterize patients who most clearly benefited from these procedures. Clinicopathologic and treatment characteristics were assessed for associations with survival. Results: Sixty-two patients met inclusion criteria, of whom 44 survived >24 months and 18 survived <12 months. Patients with extended survival were less likely to have functioning tumors ( p  = 0.047), had fewer liver metastases ( p  = 0.047), and a longer disease-free interval (DFI) (median 17.6 vs 2.3 months, p  < 0.0001). On multivariable analysis, DFI (OR = 1.33, 95% CI = 1.12–1.58) and non-functioning tumor (OR = 0.13, 95% CI = 0.13–0.56) were independently associated with prolonged survival. Conclusion: Metastasectomy/ablation should be considered for patients with ACC liver metastases. DFI and tumor functional status may be useful in selecting optimal candidates for these procedures.